Interplay of endoplasmic reticulum stress and autophagy in neurodegenerative disorders. Issue 2 (1st February 2016) - Cai, Yu; Arikkath, Jyothi; Yang, Lu; Guo, Ming-Lei; Periyasamy, Palsamy; Buch, Shilpa
ABSTRACT: The common underlying feature of most neurodegenerative diseases such as Alzheimer disease (AD), prion diseases, Parkinson disease (PD), and amyotrophic lateral sclerosis (ALS) involves accumulation of misfolded proteins leading to initiation of endoplasmic reticulum (ER) stress and stimulation of the unfolded protein response (UPR). Additionally, ER stress more recently has been implicated in the pathogenesis of HIV-associated neurocognitive disorders (HAND). Autophagy plays an essential role in the clearance of aggregated toxic proteins and degradation of the damaged organelles. There is evidence that autophagy ameliorates ER stress by eliminating accumulated misfolded proteins. Both abnormal UPR and impaired autophagy have been implicated as a causative mechanism in the development of various neurodegenerative diseases. This review highlights recent advances in the field on the role of ER stress and autophagy in AD, prion diseases, PD, ALS and HAND with the involvement of key signaling pathways in these processes and implications for future development of therapeutic strategies.